Affirmative action and human capital investment: Theory and evidence from a randomized field experiment - Christopher Cotton; Brent R. Hickman; Joseph P. Price (Queen's University, Department of Economics, 2015)
Pre-College human capital investment occurs within a competitive environment and depends on market incentives created by Affirmative Action (AA) in college admissions. These policies affect mechanisms for rank-order allocation of college seats, and alter the relative competition between blacks and whites. We present a theory of AA in university admissions, showing how the effects of AA on human capital investment differ by student ability and demographic group. We then conduct a field experiment designed to mimic important aspects of competitive investment prior to the college market. We pay students based on relative performance on a mathematics exam in order to test the incentive effects of AA, and track study efforts on an online mathematics website. Consistent with theory, AA increases average human capital investment and exam performance for the majority of disadvantaged students targeted by the policy, by mitigating so-called "discouragement effects." The experimental evidence suggests that AA can promote greater equality of market outcomes and narrow achievement gaps at the same time.
Keywords: J15; J24; C93; D82; D44; 330; Affirmative Action; College Admissions; Field Experiment; Human Capital; All-Pay Auction